Acting Across Borders Mobility and Identity in Italian Cinema - Zambenedetti, Alberto (Edinburgh University Press, 2022)
Sheds new light on the notion of Italian identity as it is understood by the national cinemaCombines Film Studies with the Mobilities FrameworkLooks at previously unexplored facets of Amedeo Nazzari's and Alberto Sordi's careersExplores a variety of physical, ideological and social 'borders' in the 'cinematic bodies' of Nazzari and SordiStudying the careers of popular actors Amedeo Nazzari and Alberto Sordi, Acting Across Borders explores the question of how Italian cinema from the 1930s to 1980s has considered human mobility. Through close readings of a selection of films, Alberto Zambenedetti examines the concept of italianità (Italian-ness) as manifested in contexts related to migration, diaspora, exile, tourism, travel and their supporting infrastructures. In this wide-ranging study, the methodologies of Film Studies and the Mobilities Framework are combined to illuminate an undertheorised yet vital tradition in the history of the national cinema